MANAJEMEN PERUBAHAN INDIVIDU DALAM IMPLEMENTASI STRATEGI ORGANISASI: INTEGRASI MODEL LEWIN, ADKAR, DAN THEORY OF PLANNED BEHAVIOR - Sahrul Sabirin; Ade Kostaman; Sedar Tarigan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The success of organizational strategy implementation is determined not only by the quality of strategy formulation but also by the organization's ability to manage change at the individual level. Many organizations fail to implement strategies effectively because employees lack the readiness, competence, and commitment required to support organizational change. This article aims to analyze the role of individual change in organizational strategy implementation through the integration of Lewin’s Change Model, the ADKAR Model, and the Theory of Planned Behavior (TPB). This study employs a library research method using a descriptive-analytical approach. The findings indicate that individual change acts as a critical bridge between strategy formulation and strategy implementation. The integration of the three models provides a comprehensive framework for understanding individual change processes, ranging from awareness development and capability enhancement to reinforcement of sustainable behavioral change. Leadership, organizational communication, and organizational culture are also identified as important supporting factors. These findings highlight the importance of positioning individual change management as an integral part of organizational strategy implementation.